Debt Policy in Ukraine: Realities and Prospects - Bench Liliia Ya.; Kornatska Roksolana M. (Bìznes Inform, 2014)
The article speaks about specific features of debt policy of Ukraine in the post-crisis period. It focuses on a necessity of stabilisation of the debt situation in countries with different levels of socio-economic development. It marks out reasons and analyses measures realised by governments for strengthening the country’s solvency and ensuring the budget space required for economic development. It analyses individual risks of the debt portfolio of Ukraine that are of top importance in the process of the state debt management. These risks include the risk of high share of debt in the debt structure, risk of the level of development of internal market of borrowings, etc. Taking into account the world progressive technologies of realisation of the debt policy the article offers directions of improvement of the state debt management in Ukraine. This would allow use of the potential of debt finances as an efficient tool of ensuring macro-financial stability and sustainable economic growth.